The Central Experimental Farm and the horticultural history collections of Faith Fyles and Isabella Preston - Aults, Erin; Knight, William (Scientia Canadensis, 2024)
This article highlights the artifactual and archival collections related to Canadian horticulturalist Isabella Preston and botanist-artist Faith Fyles, who both pursued careers at the Central Experimental Farm in Ottawa in the early twentieth century. These collections, held at the Royal Botanical Gardens in Burlington, Ontario and the Ingenium collection in Ottawa, provide materials for researchers interested in women as producers of horticultural knowledge in Canadian agriculture.